Recent advancements in M2M communications in 4G networks and evolution towards 5G - Ratasuk, Rapeepat; Prasad, Athul; Zexian Li; Ghosh, Amitava; Uusitalo, Mikko (2015 18th International Conference on Intelligence in Next Generation Networks, 2015)
Machine-to-Machine (M2M) communications is considered to be one of the key enablers for the provisioning of advanced applications and services such as smart cities and hospitals, as well as automated vehicular and industrial automation operation. Currently, in LTE-Advanced systems, the main focus has been on supporting massive deployment of low cost devices, with enhanced radio access network coverage. In this work, we present the recent MTC enhancements in LTE system. Detailed performance analysis based on LTE system settings is also presented. The LTE capacity evaluations performed based on devices per physical resource block indicate that significantly large number of devices can already be supported in an LTE system, based on the assumptions used, with minimal system overhead. We also present an overview of some of the key scenarios, requirements and use cases currently being considered for M2M communication in fifth generation (5G) systems. The performance requirements currently being considered for massive and ultra-reliable M2M communication are also discussed.